Pengaruh Citra Merek Terhadap Minat Beli Konsumen - Anggi Latif Saputra; Tia Aprilia (Papanda Publisher, 2023)
Brand image is one of the components that influence consumer purchase intention. Competitive companies use brand image to attract attention and generate interest in buying new customers, as well as retaining existing customers. This study aims to determine brand image that influences consumer buying interest. The method in this study is a descriptive method with survey techniques and verification methods. This research was conducted at Lidia Cake & bakery cake shop. The data collection instrument used a questionnaire with a total of 13 questions which were distributed to 96 respondents as the research sample. The results showed that more than 50% of respondents chose very attractive alternative answers to statements regarding the brand image. In statements regarding consumer buying interest, more than 50% of respondents chose very attractive alternative answers. The results of statistical tests, the results show that there is a positive influence of brand image on consumer buying interest to keep buying Lidia Cake & Bakery. The conclusion of this study is that brand image has a significant effect on consumer buying interest.